Mu (em-power-you) : a jewelry brand inspired by the stories of different communities - Cho, Cecilia Hyunjae (Nanyang Technological University, 2021)
M^u (pronounced: em-power-you) is a handmade jewelry brand conceived to empower and transform. Cecilia HyunJae Cho designed all components of this brand to cultivate physical and mental positive energy. M^u will release different collections inspired by a specific issue or community interests. The first collection from M^u takes inspiration from the anecdotes of Third Culture Kids (TCK). TCKs are those raised in cultures different from their birth or ethnic culture. While this lifestyle promotes a well- founded worldview and kinship with various cultures, it comes with its share of obstacles. For instance, TCKs face the deep-seated conflict of identity that stems from the insecurity of cultural values. The stories of TCKs have been transformed—by design—into ‘amulets’ for beauty and protection. The pieces in the TCK collection seek to ease the friction between clashing ideologies, values, and identities through a visual manifestation of coexisting elements of culture. Furthermore, wearing the pieces will have a physical and mental realization aligned with the mission of M^u.